Identifying Strategic Organizational Culture Factors with a Psychological Approach in Mazandaran University of Medical Sciences - Hashemi, Seyed Mehdi; Talebi, Ghasem Ali; Ranjbar, Mansour (Assessment and Practice in Educational Sciences, 2025)
The present study was conducted with the aim of identifying the strategic factors of organizational culture using a psychological approach in Mazandaran University of Medical Sciences. The study is applied in purpose and uses a mixed-methods design (qualitative–quantitative) of the sequential exploratory type. In the qualitative phase, the grounded theory method and analysis of semi-structured interviews with 25 experts in the field of public management were used, and ultimately, 12 individuals were selected as the final sample through the snowball sampling method. The data collection instrument in the quantitative phase was a researcher-made questionnaire containing 65 items across 6 dimensions and 13 components, the validity and reliability of which were confirmed through expert judgment, factor loadings, and Cronbach’s alpha. The findings indicated that organizational strategies—particularly in the dimensions of training and human development, as well as interpersonal communication—have a significant impact on the formation of an effective organizational culture with a psychological approach. The results of the structural equation modeling further showed that the strategies explain approximately 27.5% of the variance in organizational culture. Accordingly, the formulation of strategic policies based on training, interaction, and human development can serve as a foundation for establishing an effective, human-centered, and psychologically oriented culture within the organization. In conclusion, an effective organizational culture is the product of systematic interaction among strategic factors within the organizational context.